PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE QUIZ TEAM TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 4 SIJUNJUNG - Sadri, Yongki Martem; Husna, Husna; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
This study originated from the fact in SMPN 4 Sijunjung that learning is still going on in one direction so as to make the learning process less enjoyable. It resulted to lower students understanding of mathematical concepts. One of the ways that could solve this problem is to implement an active learning strategy type quiz team. This study aims to determine whether students understanding of mathematical concepts by applying active learning strategies quiz team type better than students understanding of mathematical concepts with conventional learning in class VII SMPN 4 Sijunjung. This type of research is experimental research on the subject with a random design. Research instrument is the final test in the form of essays studying containing indicator of understanding the concept. Techniques of data analysis were performed using one-way t-test with the help of MINITAB. Based on the analysis of data obtained P-value of 0.037 is less than Î± is set at 0.05. It can be concluded that the students understanding of mathematical concepts by applying active learning strategies quiz team type better than students understanding of mathematical concepts with conventional learning in class VII SMPN 4 Sijunjung.